Framing Dedi Mulyadi's Vasectomy Policy in International Media: A Comparative Analysis Using Entman's Framing Theory and Its Implications for Indonesia's Public Diplomacy - Tris Dina Susanti; Atef Fahrudin (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study examines the international media's portrayal of the vasectomy policy as a prerequisite for accessing social assistance, as proposed by West Java Governor Dedi Mulyadi. Using Robert Entman's theoretical framework, this research examines how three international media outlets (Channel News Asia, South China Morning Post, and The Telegraph) frame this controversial policy through four key elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The research method employs qualitative framing analysis with a systematic approach to the news corpus from the three media outlets. Results indicate that all three media outlets use negative framing with a dominance of moral evaluation (90%) and problem definition (85%), yet with different strategies: SCMP uses a